The socio-scientific controversies in the teaching contents of cosmetic chemistry - Parga Lozano, Diana Lineth; Romero Sánchez, Jacqueline (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article presents the results of a research project conducted at the National Pedagogical University of Bogotá, between 2014 and 2015. Said study assessed, in the current Colombian context, the curricular content of the Cosmetics Chemistry subject in the training of professionals in the field of facial and corporal aesthetics. This appraisal allowed to study the impact that being trained, or not, in this subject had on content characterization. The inductive nature of the investigation permitted, based on the analysis of collected data, to structure a macro-curricular, meso-curricular and microcurricular proposal (under socio- cientific controversies), which includes (for the national and international levels) an assessment of the subject’s positionality in the curriculum of institutions offering careers on facial and corporal aesthetics in Colombia. In relation to the utility of the results of this research work, it pretends to suggest to the national ministry of education to consider these results for the convenient establishment of academic policies on the matter.